PENGARUH BUDAYA ORGANISASI DAN PENGALAMAN KERJA TERHADAP KINERJA PEGAWAI DAN NON PEGAWAI PADA KELURAHAN DESA CICALENGKA - Galuh Adjie Saputra; Darmadi Darmadi (CV. Denasya Smart Publisher, 2025)
This study aims to determine the influence of organizational culture and work experience on the performance of employees and non-employees in Cicalengka Village. The research method used is quantitative, employing primary data. Data collection was carried out through questionnaires distributed to 66 respondents comprising all employees and non-employees of Cicalengka Village. The analytical methods used include descriptive analysis, data instrument testing, classical assumption tests, simple and multiple linear regression analysis, correlation coefficient testing, coefficient of determination testing, and hypothesis testing using t-test and F-test with SPSS version 29. The results of the study show that, partially, organizational culture has a positive influence on employee performance with a t-value of 8.591 > t-table value of 1.998 and a significance value of 0.001 < 0.05. Meanwhile, work experience also has a positive influence on employee performance with a t-value of 10.797 > t-table value of 1.998 and a significance value of 0.001 < 0.05. Simultaneously, organizational culture and work experience have a positive influence on employee performance with an F value of 63.422 > F-table value of 3.14 and a significance value of 0.001 < 0.05. The coefficient of determination (R²) of 66.8% indicates that employee performance is influenced by organizational culture and work experience, while the remaining 33.2% is influenced by other factors not examined in this study.